Evaluating the Effectiveness of Health Communication in Predicting Menstrual Health Outcomes in India - Amala T. Chacko , Jolly Jose , Parul Mehta (South Eastern European Journal of Public Health, 2025)
Research on health communication interventions for menstrual health promotion in India remains relatively unexplored. Strategic communication is widely acknowledged as a powerful tool for shaping health behaviors and driving societal change. In India, various initiatives addressing menstrual health and hygiene operate at multiple levels, starting from grassroots efforts. This expanded study builds upon our previous work presented at the International Conference on Sustainable Development Goals (ICSDG). It aims to evaluate a broad spectrum of published research that has examined the effectiveness of communication interventions in shaping menstrual health practices among women and adolescent girls in India. By reviewing studies from databases such as PubMed, Medline, Ovid, Sage Journals, Science Direct, Springer, Taylor & Francis, DOAJ, and Google Scholar, we identify key insights into the outcomes of Social and Behaviour Change Communication (SBCC), Behaviour Change Communication (BCC), Information, Education, and Communication (IEC), and interpersonal communication strategies. The findings indicate that these interventions have successfully enhanced menstrual health awareness among adolescents and women of reproductive age, leading to positive behavioral and attitudinal changes.